2006
DOI: 10.1016/j.ejheart.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating levels of heat shock protein 70 are related to systemic inflammatory reaction through monocyte Toll signal in patients with heart failure after acute myocardial infarction

Abstract: Background: Recent studies have shown that heat shock protein (HSP) 70 may serve as a ''damage signal'' to the immune system and could be the endogenous ligand for Toll-like receptor (TLR) 4 mediating synthesis of inflammatory cytokines. Aims: To explore the relationship between circulating HSP70 levels and activation of monocyte TLR4 and myocardial damage after AMI. Methods and results: This study examined circulating HSP70 and monocyte TLR4 levels in 52 patients with AMI and 20 controls, and analyzed ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 25 publications
2
63
2
6
Order By: Relevance
“…The values represent mean ± SD (n = 3). *p < 0.05 significantly different from control, + p < 0.05 significantly different from 45 mg F − -treated rats (one-way ANOVA followed by Tukey's multiple comparison test) Earlier studies showed that elevated extracellular levels of Hsp70 serve as a prognostic marker for inflammatory cytokine-mediated immune response and the progression of heart failure in patients with acute AMI (Jenei et al 2013;Satoh et al 2006). Our results are in accordance with the report of Chattopadhyay et al (2011).…”
Section: Resultssupporting
confidence: 83%
“…The values represent mean ± SD (n = 3). *p < 0.05 significantly different from control, + p < 0.05 significantly different from 45 mg F − -treated rats (one-way ANOVA followed by Tukey's multiple comparison test) Earlier studies showed that elevated extracellular levels of Hsp70 serve as a prognostic marker for inflammatory cytokine-mediated immune response and the progression of heart failure in patients with acute AMI (Jenei et al 2013;Satoh et al 2006). Our results are in accordance with the report of Chattopadhyay et al (2011).…”
Section: Resultssupporting
confidence: 83%
“…EGR-1 mediates the synthesis and release of HSP70 into the extracellular environment (46). In response to stressors such as myocardial infarction, HSP70 is released into the circulation and promotes the increase of TLR4 levels in patients, thereby triggering NF-kB signaling and proinflammatory cytokine production (52,53). Further studies are thus needed to elucidate the roles of extracellular mediators such as HSP in EGR-1-associated proinflammatory chemokine production in response to Nod2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…One day after AMI, the elevated Hsp70 levels showed a moderate positive correlation with IL-6 and IL-8, with TNF-α and the levels of the Toll like receptor 4, although the association was absent in healthy control subjects. Circulating Hsp70 levels were positively related to markers of myocardial damage including cardiac troponin T and creatine kinase MB (Dybdahl et al 2005;Satoh et al 2006). Hsp70 can be released into the extracellular environment not only in response to tissue damage but also under physiologic conditions (Pockley et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognised that Hsp70 are present in the peripheral circulation of healthy individuals (Pockley et al 1998;Dhingra et al 2006), and their levels increase after intensive exercise (Febbraio et al 2002;Fehrenbach et al 2005). Elevation of serum Hsp70 was reported in patients with soft tissue trauma (Pittet et al 2002;Flohe et al 2007), with peripheral and renal vascular disease (Wright et al 2000), after acute myocardial infarction (AMI; Dybdahl et al 2005;Satoh et al 2006), or coronary artery bypass grafting (Dybdahl et al 2002), preeclampsia (Molvarec et al 2006) and haemolytic anemia elevated liver enzymes low platelet count (HELLP) syndrome (Molvarec et al 2007). Genth-Zotz et al (2004) found elevated serum Hsp70 levels in CHF patients and a correlation between the Hsp70 and disease severity and cachexia, but not with survival.…”
Section: Introductionmentioning
confidence: 99%